Age-dependent removal of Atg9-containing vesicle accumulations in motoneuron disease models by physical exercise - Veh, Alexander; Ewald, Melissa; da Cruz Neris Geßner, Vinicius; Giridhar, Neha Jadhav; Hutchings, Amy-Jayne; Stigloher, Christian; Binotti, Beyenech; Heinze, Katrin Gertrud; Lüningschrör, Patrick (Translational neurodegeneration, 2025)
Background: Atg9-containing vesicles are enriched in synapses and undergo cycles of exo- and endocytosis similarly to synaptic vesicles, thereby linking presynaptic autophagy to neuronal activity. Dysfunction of presynaptic autophagy is a pathophysiological mechanism in motoneuron disease (MND), which leads to impaired synaptic integrity and function. Here, we asked whether boosting neuronal activity by physical exercise modulates the cellular and motor phenotypes of Plekhg5-deficient mice, an MND model with defective presynaptic autophagy. Methods: To characterize the vesicle accumulations in Plekhg5-deficient mice, we performed immunohistochemical staining, electron microscopy, and super-resolution imaging. Following voluntary running wheel exercise, we quantified the histopathological changes within the spinal cord and at neuromuscular junctions using an unbiased machine-learning approach. Additionally, we analyzed the motor performance of the animals by measuring their grip strength. To assess changes in the autophagic flux upon physical exercise in vivo, we utilized mRFP-GFP-LC3 expressing mice. The presence of Atg9-containing vesicle clusters in SOD1G93A was analyzed to examine the relevance of this pathological feature in a second MND model. Results: We found marked accumulations of Atg9-containing vesicles at presynaptic sites of Plekhg5-deficient mice, which could be cleared by four weeks of voluntary running wheel exercise in young but surprisingly not in aged Plekhg5-deficient mice. However, physical exercise in aged mice led to synaptic vesicle sorting into the Atg9-containing vesicle accumulations without their removal. In line with these findings, short-term voluntary exercise triggered motoneuron autophagy in young but not old mice. Pointing to a broader role of Atg9-containing vesicles in the pathophysiology of MND, we also found Atg9-containing vesicle accumulations in SOD1G93A mice, a well-established ALS model. Strikingly, physical exercise in presymptomatic SOD1G93A mice resulted in a reduction of the vesicle accumulations. Conclusions: Our data highlight the essential role of Atg9 in presynaptic autophagy and suggest that boosting autophagy by physical exercise provides a tool to maintain presynaptic function at the early but not late stages of Plekhg5-associated MND and possibly amyotrophic lateral sclerosis.